Contests and unethical behavior in organizations: a review and synthesis of the empirical literature - Simon Piest; Philipp Schreck (Management Review Quarterly, 2020)
Contests are widely used in business contexts because they are believed to increase the effort and performance levels of employees. One negative aspect of contests is that they may provide incentives for unethical behavior aimed at improving one's own position relative to that of competitors. It is therefore important to understand how companies should design contests so as to reduce unethical behavior without reducing the positive effects of contests on employee effort. Research from the social and behavioral sciences can offer relevant insights on this question, as in those fields competition is a subject of sustained academic interest. The aim of this review is to offer a systematic account of the growing literature on contests and unethical behavior and shed light on why and when contests among employees may lead to unethical behavior. To this aim, we also develop a framework for organizing the vast, multi-disciplinary literature in a structured and integrative manner. Through this endeavor, our review identifies several directions for future research.
Keywords: M12; M14; M52; 650; Behavioral business ethics; Cheating; Competition; Competitiveness; Sabotage; Tournament